ESP Teachers’ Beliefs and Practices in Fostering Autonomous Learning: A Study on Motivation among Non-English Major Students - Hadriani Hadriani; Titin Rahmiatin Rahim; Andi Rachmawati Syarif (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study aims to explore ESP teachers' beliefs and practices in fostering autonomous learning through assessing students' motivation in non-English majors. The sampling method used convenience sampling. One lecturer at Universitas Muhammadiyah Kendari who teaches at the Faculty of Agriculture was recruited as a participant. Data were collected using questionnaires and interviews, which were adapted from Yang and Wyatt (2021) and focused on understanding student motivation as well as the practices implemented. Data analysis was conducted using qualitative and evaluative approaches. The results showed that the implementation of project-based learning (PBL) was very effective in motivating students to learn Autonomously. Although initially students had limitations in English speaking ability, structured support and practical activities helped them feel more confident. Future research is recommended to explore other learning methods that can increase students' motivation and engagement, such as collaboration-based learning and the use of digital technology.